Synthesis and Identification of Mono and Bicyclic Compounds Containing Dinitrogen Atoms as Anesthetic . - Nagham. Mahmood. Aljamali (Al-Qadisiyah Journal of Pure Science, 2017)
In this study , mono & bicyclic compounds [1-8] were synthesized by alkalytion of 2-aminothiozoline with carbonyl compounds (succinic acid ., chloro acetic acid .,2,5-hexan-dione ., 3-chloro propoyl chloride ), where as the compounds [9-12] were synthesized by condensation between diketone compounds with (2-amino benzothiazole ,guanine) . The synthesized compounds structures were characarterized by several methods :{(C.H.N)-analysis , FT.IR-spectra , H.NMR-spectra } & melting points .